Front Cover: Nuclear Aurora kinase A triggers programmed death‐ligand 1‐mediated immune suppression by activating MYC transcription in triple‐negative breast cancer. Issue 9 (14th September 2021) - Sun, Shulan; Zhou, Wei; Li, Xiaoxi; Peng, Fei; Yan, Min; Zhan, Yajing; An, Fan; Li, Xiaoyan; Liu, Yunyong; Liu, Quentin; Piao, Haozhe
Abstract : The cover image is based on the Original Article Nuclear Aurora‐A triggers programmed death ligand 1 mediated immune suppression by activating MYC transcription in triple‐negative breast cancer by Quentin Liu et al., https://doi.org/10.1002/cac2.12190 .